God becoming human: Incarnation in the Christian bible - Feldmeier, Reinhard (Baylor University Press, 2021)
"Surveys the various ways Scripture depicts the mediation of the divine to humanity, situating the Christian doctrine of incarnation at the center of God's will for reconciliation and for full human flourishing"--